Green Supply Chain Management Organizational Performance - Sinaga, Obsatar; Mulyati, Yati; Darrini, Anni; Galdeano, Dulcenombre Madrid; Prasetya, Arus Reka (ExcelingTech, 2019)
The purpose of this study is to ensure the organizational performance through internal and external drivers along with the mediating role of green supply chain management on Indonesian manufacturing industry. 5point Likert scale is used to collect the data. Random sampling technique is used on the 300 respondents from Indonesian medical officers. PLS3 is used to analyze the data. The findings of this concluded that internal drivers and external drivers are strong motivators for â€œSmall and Medium-Sized Enterprises (SMEs)â€ to practice. â€œGreen supply chain managementâ€ practices such as management of internal environmental, cooperation and green purchasing with consumers are in practice in Indonesian â€œSmall and Medium-Sized Enterprises (SMEs)â€. SMEs that practicing â€œGreen supply chain managementâ€ may expand company repute and consequence in higher loyalty with improved sales, and increased profit.